The influence of intensity and neuropathic component of pain syndrome on the quality of life in patients with multiple sclerosis - T. I. Nehrych; N. L. Bozhenko; M. I. Bozhenko (Zaporožskij Medicinskij Žurnal)
The aim of the work. To analyze the influence of intensity and neuropathic component of pain syndrome on the quality of life structure characteristics in patients with multiple sclerosis (MS).